Gambling in Malaysia : adequacy and relevancy of policy, law and controls / Muhammad Razeef Hamzah…[et al.] - Hamzah, Muhammad Razeef; Zabri, Shahril Redha; Mahzan, Muhammad Nur Fadzli; Hussin, Zool Hilmi (2009)
Gambling contributes an average of RM2 billion annually to the government. Malaysia has a strict suppressive policy on gambling and the existence of various legislation on gambling however it does not have the effect of deterring gambling associated problems. Illegal gambling activities or gambling without license however has flourished and the number of Muslims and underage involved in gambling activities are increasing. The farther imminent threats to the society are posed by online gambling and sports gambling. This research looked into the adequacy and relevancy of policy, law and control mechanism by analyzing the related provisions in Statutes together with the perspectives and the views of licensing officers in the Ministry of Finance, enforcement officers, legal practitioners, gambling operators and also by making comparisons with the policies and approaches adopted by Singapore and United Kingdom. Guidelines and standards of practice from other countries on gambling must be studied to ensure that the public is protected against the evil of gambling. Suggested recommendations include public awareness campaigns, amendments to statutes to include statutory duties on the part of gambling operators, increasing the penalties and introducing zoning regulations. The said proposed recommendations should be adequate to improve control and to cater for the present and future control needs by providing a basis for further researches.